Rancang Bangun Aplikasi Manajemen Klien Pada Paris (Parking Information System) - Setiawan, Ardy; Amelia, Tan; Santoso, Rudi (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Paris (Parking Information System) is a information system to deal with parking security and performance. Paris can handle parking transaction with one area one Paris online and offline. It is not efficient anymore if have more than one parking area in far location that cannot connected properly. It must doing update or making report in all parking area. All parking area must be connected and can be communicated. Paris Management Client is a application for connecting all Paris. Offline Paris and online Paris can synchronize data. Member data can distributed in all area with one insert. Not only that, parking member can get parking availability information from Paris Management Client because offline Paris always communicated with online Paris in some interval of time. Paris Management Client developed with waterfall SDLC method. Starts with analysing system’s need, then making a system design, coding application, and then testing application. The result is Paris Management Client can help SSI as developer to control all Paris, help client to update data or make report, and help member to get parking’s slot easily. recommendation for Paris is develop mobile application for member that can be give information visually, not only text.